Nutrient Partitioning and Dynamics in Coriaria nepalensis Wall Dominated Shrublands of Degraded Hills of Kumaun Himalaya - Awasthi, Pankaj; Bargali, Kiran; Bargali, Surendra Singh; Khatri, Kavita; Jhariya, Manoj Kumar (Frontiers in Forests and Global Change, 2022)
Coriaria nepalensis is one among the shrubs which mitigate the frequency of perilous natural events or natural calamities by its ability. The present work elucidates the nutrient dynamics of C. nepalensis shrublands in degraded hills of Kumaun Himalaya. The average nutrient concentration (N, P and K) in aboveground components of C. nepalensis was in the order: Foliage > Twigs > Branches > Bole wood whereas in belowground components the order was: Fine roots > Lateral roots > Stump root. The general order of vegetation on the basis of percent contribution to total nutrient storage was: Tree > Herbs > Shrubs. Proportion of nutrients stored in shrub layer was: 18.24-41.37% N, 2.63-8.33% P, 16.76-30.96% K of total vegetation nutrient stock. The soil stored maximum proportion of nutrients at each site (79.48-87.54% N, 70.47-87.88% P, 74.33-88.27% K). Maximum nutrient storage in soil and vegetation was recorded for site 3 and minimum for site 1.The uptake of N, P and K by vegetation ranged from 428-1353 kg ha-1 yr-1, 32-102 kg ha-1 yr-1 and 109-479 kg ha-1 yr-1, respectively. In the present study, the turnover time was 1.06-1.33 yrs for N, 1.03-1.15 yrs for P and 1.02-1.13 yrs for K. Compartment models reflects the distribution of nutrients and net annual flux of the site that will helps to develop the management plan at site level to maintain the fertility and productiveness of the site.